Composite film humidity sensor based on ternary semiconductor metal oxide and preparation method thereof
By using ALD technology to deposit Sn-Ti-Zn-O ternary semiconductor metal oxide film in humidity sensors, the problem of long response and recovery time of existing humidity sensors is solved, and high sensitivity, fast response and wide detection range is achieved Effective, while reducing manufacturing costs.
Patent Information
- Application Number
- CN202411510190.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-07
AI Technical Summary
The existing humidity sensors have too long response and recovery time, and are costly to manufacture due to the need for precious metal modification.
ALD technology is used to deposit Sn-Ti-Zn-O ternary semiconductor metal oxide film as a moisture-sensitive material layer on an insulating substrate, achieving a high sensitivity and fast response humidity sensor without the need for precious metal modification.
The high sensitivity, fast response and wide detection range of the humidity sensor are achieved, reducing manufacturing costs and improving the stability of the sensor.
Smart Images

Figure CN119395102A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of semiconductor sensors, and in particular relates to a composite thin film humidity sensor based on a ternary semiconductor metal oxide and a preparation method thereof. Background Art
[0002] Humidity is closely related to people's daily life. The level of humidity directly affects the health status of the human body and the comfort of the human body. In the fields of industry, agriculture, forestry, medical treatment and weather forecasting, humidity monitoring and control also play a vital role. In the storage of industrial products, improper humidity can cause metal corrosion and decay of items; in agriculture and forestry, humidity directly affects the growth of crops and soil moisture; in the field of meteorology, humidity is a key factor in predicting rainfall and climate change; and in the field of medicine, humidity is not only related to the success of anesthesia surgery, but also can be used as an important means of diagnosing diseases by monitoring the humidity of exhaled gas. Therefore, it has become an urgent task to develop high-performance humidity sensors to achieve accurate and fast humidity monitoring to meet the needs of different fields.
[0003] Semiconductor metal oxides are widely used as humidity-sensitive materials due to their excellent electrical properties, good chemical stability, simple and green preparation process, and low cost. 2 , ZnO, TiO 2 As a common humidity-sensitive material, it has strong hydrophilicity and high sensitivity, and has attracted widespread attention. However, single semiconductor metal oxide humidity sensors usually have disadvantages such as long response and recovery time. Generally, expensive precious metals such as Au and Pt are used as catalysts for modification to speed up the response / recovery rate, which is bound to significantly increase the manufacturing cost.
[0004] As an advanced material preparation technology, atomic layer deposition (ALD) technology has received special attention in the fields of microelectronics, optoelectronics, energy catalysis, etc. in recent years, especially in the field of integrated circuits. ALD is a method of forming a thin film by alternately passing gas-phase precursor pulses into the reaction chamber to cause a chemical adsorption reaction on the substrate surface. By using its unique self-limiting and self-saturation characteristics, it can achieve precise control of the thickness and composition of the film at the atomic scale, ensuring the excellent three-dimensional conformality and large-area uniformity of the film, which is crucial to improving the sensitivity and response speed of humidity sensors and optimizing sensing performance. In addition, due to the characteristics of ALD technology, it is very suitable for compatibility with microelectromechanical (MEMS) systems to prepare ultra-thin, composite and integrated multifunctional sensors. Summary of the invention
[0005] The present invention provides a composite thin film humidity sensor based on ternary semiconductor metal oxide and a preparation method thereof. A ternary semiconductor metal oxide thin film is deposited on an insulating inorganic or polymer substrate using ALD technology as a humidity sensitive material layer. In the absence of noble metal modification, a humidity sensor with high sensitivity, fast response / recovery, wide detection range and good stability is obtained, thereby solving the problem of long response / recovery time of existing humidity sensors.
[0006] To achieve the above objectives, the present invention adopts the following technical solutions: A composite thin film humidity sensor based on ternary semiconductor metal oxide, comprising: an insulating substrate, a ternary semiconductor metal oxide humidity sensitive material layer, and a conductive electrode layer; the ternary semiconductor metal oxide humidity sensitive layer is a Sn-Ti-Zn-O ternary semiconductor metal oxide thin film, which is SnO 2 Thin film, TiO 2 Thin film, ZnO thin film, its structure is [(SnO 2 ) m (TiO 2 ) n (ZnO) o ] p , where m, n, o are all 1-10, and p is 10-500.
[0007] The method for preparing the above-mentioned composite thin film humidity sensor based on ternary semiconductor metal oxide comprises the following steps: (1) Ultrasonic cleaning of the insulating substrate was performed with acetone, isopropanol, anhydrous ethanol, and deionized water in sequence for 5 minutes, and then blown dry with high-purity nitrogen (99.999%) for later use; (2) On the cleaned insulating substrate, m-cycle SnO is deposited using ALD technology 2 film; (3) After depositing m-cycle SnO 2 On the substrate of the thin film, n-cycle TiO is deposited by ALD technology 2 film; (4) After depositing m-cycle SnO 2 and n-cycle TiO 2 On the substrate of the film, o-cycle ZnO thin film is deposited by ALD technology; (5) Repeating steps (2) to (4), taking steps (2) to (4) as a sub-cycle, and depositing p super-cycles by ALD technology to obtain a Sn-Ti-Zn-O ternary semiconductor metal oxide composite film with a thickness of 20-85 nm; (6) Using a mask, a metal interdigitated electrode with a thickness of 100-200 nm is deposited on the Sn-Ti-Zn-O ternary semiconductor metal oxide film as a conductive electrode. After wiring and packaging, a Sn-Ti-Zn-O ternary semiconductor metal oxide composite thin film humidity sensor can be obtained.
[0008] In the above steps, the insulating substrate is an inorganic substrate or a polymer substrate; The temperature of the ALD deposition is from room temperature to 120°C; The tin source used was tetrakis(dimethylamino)tin (TDMSn) or SnCl 4 ; The titanium source used was titanium tetrachloride (TiCl 4 ) or tetrakis(dimethylamino)titanium (TDMAT); The zinc source used was diethylzinc (DEZ) and the oxygen source was water or plasma oxygen.
[0009] Beneficial effects: The present invention provides a composite thin film humidity sensor based on ternary semiconductor metal oxide and a preparation method thereof. A Sn-Ti-Zn-O ternary semiconductor metal oxide thin film is prepared on a substrate by ALD technology. The Sn-Ti-Zn-O ternary semiconductor metal oxide thin film plays an important role in humidity detection as a core humidity sensitive layer. A heterojunction is formed between the ternary semiconductor metal oxides, which promotes the migration of electrons on the sensor surface and increases the surface depletion layer, thereby increasing the initial resistance value of the sensor. As the relative humidity (RH) increases, water molecules gather and react near the depletion layer, reducing the interface potential barrier and significantly reducing the resistance value of the sensor, which helps to improve the sensitivity of the sensor, the response recovery speed and the response performance under low humidity. Moreover, the surface of the ternary semiconductor metal oxide thin film contains more oxygen vacancies, which improves the sensitivity of the material to water molecules, promotes the adsorption of more water molecules, accelerates the dissociation rate of water molecules, and forms more hydroxyls. According to the ionic conductivity theory, the OH on the surface of the material - H +It will combine with other water molecules in the form of hydrogen bonds to form physical adsorption, and this physical adsorption will continue to form the first, second...physical adsorption layer, so that the sensor can have a good response to high humidity, so that the humidity sensor of the present invention has a wide detection range. The preparation method of the present invention obtains a humidity sensor with high sensitivity, fast response / recovery, wide detection range and good stability without precious metal modification, achieves high sensitivity to different humidity, effectively improves the response / recovery speed, and has a wide range and stability. Compared with traditional precious metal modified semiconductor metal oxide humidity sensors, the cost is greatly reduced. The humidity sensor of the present invention has a simple structure, and the ALD preparation process is compatible with the microelectronic process, which provides a reliable technical foundation for the future development of integrated, miniaturized and intelligent humidity sensors. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 (a) is a schematic diagram of the structure of the Sn-Ti-Zn-O ternary semiconductor metal oxide composite thin film humidity sensor in an embodiment of the present invention: 1-insulating substrate; 2-ALD deposited Sn-Ti-Zn-O ternary semiconductor metal oxide thin film; 3-interdigitated electrodes; Figure 1 (b) is a schematic diagram of the structure of the Sn-Ti-Zn-O composite film deposited by ALD in the present invention; Figure 2 Schematic diagram of the mask of the interdigitated electrode in the embodiment of the present invention: 5-the white part represents the metal material of the mask; 6-the black part represents the gap of the mask; 7-the tooth length of the interdigitated electrode; 8-the gap length of the interdigitated electrode teeth; 9-the tooth width of the interdigitated electrode; 10-the width of the interdigitated electrode; 11-the length of the interdigitated electrode; Figure 3 (a) is the current-time curve of the Sn-Ti-Zn-O ternary semiconductor metal oxide composite thin film humidity sensor sample in the embodiment of the present invention at relative humidity of 11%, 23%, 44%, 59%, 75%, 85% and 98% respectively; Figure 3 (b) is the linear relationship diagram between current and relative humidity; Figure 4 The current-time curves of the Sn-Ti-Zn-O ternary semiconductor metal oxide composite thin film humidity sensor sample during rapid breathing and normal breathing in the embodiment of the present invention are shown; Figure 5 This is a long-term stability test curve of the Sn-Ti-Zn-O ternary semiconductor metal oxide composite thin film humidity sensor sample under a relative humidity of 98% in an embodiment of the present invention. DETAILED DESCRIPTION
[0011] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments: Example 1
[0012] like Figure 1 and Figure 2 As shown, a composite thin film humidity sensor based on ternary semiconductor metal oxide includes: SiO 2 / Si substrate, Sn-Ti-Zn-O ternary semiconductor metal oxide film, Pt interdigital electrode; Sn-Ti-Zn-O ternary semiconductor metal oxide film from bottom to top is SnO 2 Thin film, TiO 2 Thin film, ZnO thin film.
[0013] The method for preparing the humidity sensor comprises the following steps: (1) Select SiO 2 / Si was used as the substrate of the sensor, which was placed on a cleaning rack, which was then placed in a beaker. Acetone, isopropanol, anhydrous ethanol, and deionized water were then used for ultrasonic cleaning for 5 minutes respectively. 2 / The Si substrate is blown dry with high-purity nitrogen (99.999%) and set aside; (2) ALD is used to clean the SiO 2 / m=2 cycle SnO deposited on Si substrate 2 The film was deposited at 120 °C, and the precursor sources used were tetrakis(dimethylamino)tin (TDMSn) and water (H 2 O), its pulse time and cleaning time are 0.2 s and 6 s respectively; (3) Based on step (2), n=2 cycle TiO is deposited using ALD technology 2 The deposition temperature was 120 °C, and the precursor sources used were titanium tetrachloride (TiCl 4 ) and water (H 2 O), its pulse time and cleaning time are 0.1 s and 4 s respectively; (4) Based on step (3), ALD technology was used to deposit o=1 cycle ZnO thin film at a deposition temperature of 120 °C. The precursor sources used were diethylzinc (DEZ) and water (H 2 O), its pulse time and cleaning time are 0.1 s and 4 s respectively; (5) Taking steps (2), (3), and (4) as a sub-cycle, repeat steps (2), (3), and (4) using ALD technology, and the super-cycle number p is 160 cycles.
[0014] (6) The interdigital electrode mask is placed tightly against the sample after step (5), and then ~100 nm thick metal platinum (Pt) is sputtered as a conductive electrode using magnetron sputtering. After wiring and packaging, it can be used as a sensitive element for detecting humidity.
[0015] Figure 3 The current-time curves of the Sn-Ti-Zn-O ternary semiconductor metal oxide composite thin film humidity sensor sample at relative humidity of 11%, 23%, 44%, 59%, 75%, 85%, and 98% respectively show that the sample has ultra-high sensitivity to different relative humidity in the wide range of relative humidity of 11%-98%. 测试湿度 -I 初始湿度 ) / I 初始湿度 Response (S 23% =12, S 44% =22, S 59% =34, S 75% =112, S 85% =146, S 98% =177), where the initial humidity is 11%, with ultra-fast response speed (when the relative humidity is 23%, 44%, 59%, 75%, 85%, and 98%, the response time is 11 s, 23 s, 68 s, 77 s, 79 s, and 45 s, respectively) and recovery speed (when the relative humidity is 23%, 44%, 59%, 75%, 85%, and 98%, the recovery time is 19 s, 17 s, 16 s, 25 s, 23 s, and 27 s, respectively), indicating that the humidity sensor prepared above has excellent humidity-sensitive performance.
[0016] Figure 4 The current-time curves for rapid breathing and normal breathing corresponding to the Sn-Ti-Zn-O ternary semiconductor metal oxide composite thin film humidity sensor sample clearly show the electrical signals of different breathing frequencies (rapid breathing and normal breathing), where the electrical signal changes faster for rapid breathing than for normal breathing, while the breathing cycle of normal breathing is longer and the electrical signal intensity is higher. Therefore, different electrical signal patterns can directly identify different breathing states. These results confirm that the humidity sensor prepared above can be used for real-time humidity monitoring during breathing.
[0017] Figure 5 This is the long-term stability test curve of the Sn-Ti-Zn-O ternary semiconductor metal oxide composite thin film humidity sensor sample under a relative humidity of 98%. b and c show the test results of the sample after 14 days and 45 days, respectively. The test sensitivity of the sample remains almost unchanged after 14 days, and even after 45 days, the sensitivity can still reach 90% of the initial value, and the sample shows good stability. Example 2
[0018] like Figure 1 and Figure 2 As shown, a composite thin film humidity sensor based on ternary semiconductor metal oxide includes: a quartz glass substrate, a Sn-Ti-Zn-O ternary semiconductor metal oxide film, and an Al interdigital electrode; the Sn-Ti-Zn-O ternary semiconductor metal oxide film is SnO 2 Thin film, TiO 2 Thin film, ZnO thin film.
[0019] The method for preparing the humidity sensor comprises the following steps: (1) Select quartz glass as the substrate of the sensor, place it on the cleaning rack, then place the cleaning rack in a beaker, and then use acetone, isopropanol, anhydrous ethanol, and deionized water to ultrasonically clean it for 5 minutes respectively. Finally, blow dry the cleaned quartz glass substrate with high-purity nitrogen (99.999%) and set it aside; (2) Deposit m=5 cycles of SnO on the quartz glass cleaned in step (1) using ALD 2 The film was deposited at 120 °C, and the precursor sources used were tetrakis(dimethylamino)tin (TDMSn) and water (H 2 O), its pulse time and cleaning time are 0.2 s and 6 s respectively; (3) Based on step (2), n=3 cycle TiO is deposited using ALD technology 2 The deposition temperature was 120 °C, and the precursor sources used were titanium tetrachloride (TiCl 4 ) and water (H 2 O), their pulse time and cleaning time are 0.1 s and 4 s respectively; (4) Based on step (3), o=4 cycles of ZnO thin film were deposited by ALD technology at a deposition temperature of 120°C. The precursor sources used were diethylzinc (DEZ) and water (H 2 O), its pulse time and cleaning time are 0.1 s and 4 s respectively; (5) Taking steps (2), (3), and (4) as a sub-cycle, repeating steps (2), (3), and (4) using ALD technology, the super-cycle number p is 120 cycles; (6) The interdigital electrode mask is placed tightly against the sample after step (5), and then ~200 nm thick metal aluminum (Al) is sputtered as a conductive electrode using magnetron sputtering. After wiring and packaging, it can be used as a sensitive element for detecting humidity. Example 3
[0020] like Figure 1 and Figure 2As shown, a composite thin film humidity sensor based on ternary semiconductor metal oxide includes: a mica substrate, a Sn-Ti-Zn-O ternary semiconductor metal oxide film, and Au interdigital electrodes; the Sn-Ti-Zn-O ternary semiconductor metal oxide film is SnO 2 Thin film, TiO 2 Thin film, ZnO thin film.
[0021] The method for preparing the humidity sensor comprises the following steps: (1) Select mica as the substrate of the sensor, place it on a cleaning rack, then place the cleaning rack in a beaker, and then use acetone, isopropanol, anhydrous ethanol, and deionized water to ultrasonically clean it for 5 minutes respectively. Finally, blow dry the cleaned mica substrate with high-purity nitrogen (99.999%) and set it aside; (2) Depositing m = 3 cycles of SnO on the cleaned mica substrate in step (1) using ALD 2 The film was deposited at 120 °C, and the precursor sources used were tetrakis(dimethylamino)tin (TDMSn) and water (H 2 O), its pulse time and cleaning time are 0.2 s and 6 s respectively; (3) Based on step (2), n=6 cycle TiO is deposited using ALD technology 2 The deposition temperature was 120 °C, and the precursor sources used were titanium tetrachloride (TiCl 4 ) and water (H 2 O), its pulse time and cleaning time are 0.1 s and 4 s respectively; (4) Based on step (3), ALD technology was used to deposit o=5 cycles of ZnO thin film at a deposition temperature of 120 °C. The precursor sources used were diethylzinc (DEZ) and water (H 2 O), its pulse time and cleaning time are 0.1 s and 4 s respectively; (5) taking steps (2), (3), and (4) as a sub-cycle, repeating steps (2), (3), and (4) using ALD technology, and the super-cycle number p is 90 cycles; (6) The interdigital electrode mask is placed tightly against the sample after step (5), and then gold (Au) with a thickness of ~150 nm is sputtered by magnetron sputtering as a conductive electrode. After wiring and packaging, it can be used as a sensitive element for detecting humidity. Example 4
[0022] like Figure 1 and Figure 2As shown, a composite thin film humidity sensor based on ternary semiconductor metal oxide includes: a polyimide (PI) substrate, a Sn-Ti-Zn-O ternary semiconductor metal oxide film, and Ag interdigital electrodes; the Sn-Ti-Zn-O ternary semiconductor metal oxide film is SnO 2 Thin film, TiO 2 Thin film, ZnO thin film.
[0023] The method for preparing the humidity sensor comprises the following steps: (1) Select PI as the substrate of the sensor, place it on the cleaning rack, then place the cleaning rack in a beaker, and then use acetone, isopropanol, anhydrous ethanol, and deionized water to ultrasonically clean it for 5 minutes respectively. Finally, blow dry the cleaned PI substrate with high-purity nitrogen (99.999%) and set it aside; (2) Deposit m = 1 cycle SnO on the PI substrate cleaned in step (1) using PEALD 2 The deposition temperature was 80 °C, and the precursor sources used were SnCl 4 and plasma oxygen, SnCl 4 The pulse time and cleaning time of plasma oxygen were 0.3 s and 15 s, respectively, and the pulse time and cleaning time of plasma oxygen were 30 s and 25 s, respectively; (3) Based on step (2), n=2 cycle TiO is deposited using PEALD technology 2 The film was deposited at 80°C. The precursor sources used were tetrakisdimethylaminotitanium and plasma oxygen. The pulse time of tetrakisdimethylaminotitanium was 0.1 s and the cleaning time was 15 s. The pulse time and cleaning time of plasma oxygen were 30 s and 25 s, respectively. (4) Based on step (3), o=2 cycle ZnO thin film was deposited by PEALD technology. The deposition temperature was 80 °C. The precursor sources used were diethyl zinc (DEZ) and plasma oxygen. The pulse time of DEZ was 0.2 s and the cleaning time was 8 s. The pulse time and cleaning time of plasma oxygen were 30 s and 25 s, respectively. (5) Taking steps (2), (3), and (4) as a sub-cycle, repeat steps (2), (3), and (4) using PEALD technology, and the super-cycle number p is 50 cycles; (6) The interdigital electrode mask is placed tightly against the sample after step (5), and then silver (Ag) with a thickness of ~150 nm is sputtered by magnetron sputtering as a conductive electrode. After wiring and packaging, it can be used as a sensitive element for detecting humidity. Example 5
[0024] like Figure 1 and Figure 2 As shown, a composite thin film humidity sensor based on ternary semiconductor metal oxide includes: a polyethylene terephthalate (PET) substrate, a Sn-Ti-Zn-O ternary semiconductor metal oxide film, and a Pt interdigital electrode; the Sn-Ti-Zn-O ternary semiconductor metal oxide film is SnO 2 Thin film, TiO 2 Thin film, ZnO thin film.
[0025] The method for preparing the humidity sensor comprises the following steps: (1) Select PET as the substrate of the sensor, place it on a cleaning rack, then place the cleaning rack in a beaker, and then use acetone, isopropanol, anhydrous ethanol, and deionized water to ultrasonically clean it for 5 minutes respectively. Finally, blow dry the cleaned PET substrate with high-purity nitrogen (99.999%) and set it aside; (2) PEALD was used to deposit m = 8 cycles of SnO on the PET substrate cleaned in step (1). 2 The deposition temperature was room temperature (25 °C) and the precursor sources used were SnCl 4 and plasma oxygen, SnCl 4 The pulse time and cleaning time of were 0.3 s and 15 s, respectively, and the pulse time and cleaning time of plasma oxygen were 30 s and 25 s, respectively; (3) Based on step (2), n=5 cycles of TiO were deposited using PEALD technology. 2 The film was deposited at room temperature (25 °C) and the precursor sources used were titanium tetrachloride (TiCl 4 ) and water (H 2 O), titanium tetrachloride (TiCl 4 ) with a pulse time of 0.3 s, a cleaning time of 15 s, and water (H 2 O) the pulse time and cleaning time are 2 s and 8 s respectively; (4) Based on step (3), o=2 cycle ZnO thin film was deposited by PEALD technology. The deposition temperature was room temperature 25°C. The precursor sources used were diethyl zinc (DEZ) and plasma oxygen. The pulse time of DEZ was 0.2 s and the cleaning time was 8 s. The pulse time and cleaning time of plasma oxygen were 30 s and 25 s, respectively. (5) Taking steps (2), (3), and (4) as a sub-cycle, repeat steps (2), (3), and (4) using PEALD technology, and the super-cycle number p is 50 cycles; (6) The interdigital electrode mask is placed tightly against the sample after step (5), and then ~100 nm thick metal platinum (Pt) is sputtered as a conductive electrode using magnetron sputtering. After wiring and packaging, it can be used as a sensitive element for detecting humidity.
[0026] The above are only preferred embodiments of the present invention, which will help those skilled in the art to further understand the present invention, but do not limit the present invention in any form. It should be pointed out that for those skilled in the art, without departing from the concept of the present invention, several modifications and improvements made are all protected by the present invention.
Claims
1. A composite thin film humidity sensor based on ternary semiconductor metal oxide, characterized in that: From bottom to top, there are an insulating substrate, a ternary semiconductor metal oxide humidity-sensitive layer, and a conductive electrode layer; the ternary semiconductor metal oxide humidity-sensitive layer is a Sn-Ti-Zn-O ternary semiconductor metal oxide film, and a heterojunction is formed between the ternary semiconductor metal oxides.
2. The composite thin film humidity sensor based on ternary semiconductor metal oxide according to claim 1, characterized in that: The ternary semiconductor metal oxide humidity sensitive layer is SnO2 film, TiO2 film, and ZnO film from bottom to top; the structure is [(SnO2) m (TiO2) n (ZnO) o ] p , wherein m, n, o are 1-10, and p is 10-500.
3. The composite thin film humidity sensor based on ternary semiconductor metal oxide according to claim 1 or 2, characterized in that: The thickness of the ternary semiconductor metal oxide humidity sensitive material layer is 20-85 nm.
4. A method for preparing a composite thin film humidity sensor based on a ternary semiconductor metal oxide, characterized in that: The following steps are involved: (1) Cleaning the insulating substrate; (2) Depositing m-cycle SnO2 thin film on the cleaned insulating substrate using ALD technology; (3) depositing an n-cycle TiO2 film on the substrate after depositing the m-cycle SnO2 film by ALD technology; (4) depositing o-cycle ZnO thin film on the substrate after depositing m-cycle SnO2 and n-cycle TiO2 thin films by ALD technology; (5) taking steps (2) to (4) as a sub-cycle, repeating steps (2) to (4) by ALD technology, depositing p super-cycles, and obtaining a Sn-Ti-Zn-O ternary semiconductor metal oxide composite film; (6) A conductive electrode is prepared on the Sn-Ti-Zn-O ternary semiconductor metal oxide film, and after lead packaging, a Sn-Ti-Zn-O ternary semiconductor metal oxide composite thin film humidity sensor is obtained.
5. The method for preparing a composite thin film humidity sensor based on a ternary semiconductor metal oxide according to claim 4, characterized in that: The ALD deposition temperature is from room temperature to 120°C.
6. The method for preparing a composite thin film humidity sensor based on a ternary semiconductor metal oxide according to claim 4 or 5, characterized in that: The tin source used for depositing SnO2 thin films using ALD technology is tetrakis(dimethylamino)tin or SnCl4.
7. The method for preparing a composite thin film humidity sensor based on a ternary semiconductor metal oxide according to claim 4 or 5, characterized in that: The titanium source used for depositing TiO2 thin films using ALD technology is titanium tetrachloride or tetrakis(dimethylamino)titanium.
8. The method for preparing a composite thin film humidity sensor based on a ternary semiconductor metal oxide according to claim 4 or 5, characterized in that: The zinc source used in the ALD deposition of ZnO thin films is diethylzinc.
9. The method for preparing a composite thin film humidity sensor based on a ternary semiconductor metal oxide according to claim 4 or 5, characterized in that: The oxygen source in ALD technology is water or plasma oxygen.
10. The method for preparing a composite thin film humidity sensor based on a ternary semiconductor metal oxide according to claim 4, characterized in that: The insulating substrate is an inorganic substrate or a polymer substrate.